Incivility at Work and its Impact on Intentions to Leave; Exploring the Mediating Role of Job Engagement - Patandung, Amos Randa; Batilmurik, Ridolof Wenand (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
This study aims to determine the mediating role of job engagement in the relationship between workplace incivility and turnover intention among nurses working at the Gatot Subroto Jakarta Army Central Hospital. The research sample consisted of 220 nurses out of a total of 606 nurses selected using a Slovin formula with a 5% margin of error. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0 software. The results of this study indicate that: 1) workplace incivility has a positive and significant effect on turnover intention; 2) workplace incivility has a negative and significant effect on job engagement; 3) job engagement has a negative and significant effect on turnover intention; and 4) job engagement mediates the relationship between workplace incivility and turnover intention.